2004
DOI: 10.1007/s10038-004-0127-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening for point mutations in the LDL receptor gene in Bulgarian patients with severe hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is a common, autosomal dominant disorder of lipid metabolism, caused by defects in the receptor-mediated uptake of LDL (low-density lipoproteins) due to mutations in the LDL receptor gene (LDLR). Mutations underlying FH in Bulgaria are largely unknown. The aim of the present study was to provide information about the spectrum of point mutations in LDLR in a sample of 45 Bulgarian patients with severe hypercholesterolemia. Exons 3, 4, 6, 8, 9, and 14, previously shown to be mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Using a study protocol as recommended by previous studies on establishing mutations in LDL-R gene, we found 18% carriers of molecular defect. 6 This result is close to what we expected based on data in previous studies (13-40% in severe hypercholesterolemia). The current results are nearer the lower limit of the range because the patients were examined only for spot mutations and polymorphisms of LDL-R but not for major rearrangements.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Using a study protocol as recommended by previous studies on establishing mutations in LDL-R gene, we found 18% carriers of molecular defect. 6 This result is close to what we expected based on data in previous studies (13-40% in severe hypercholesterolemia). The current results are nearer the lower limit of the range because the patients were examined only for spot mutations and polymorphisms of LDL-R but not for major rearrangements.…”
Section: Discussionsupporting
confidence: 92%
“…[3][4][5] The incidence of spot mutations established in this study is lower than that reported by Ganev et al in patients with moderate to severe hypercholesterolemia (18%). 3,5,6 This may be accounted for by the fact that this finding was established only in patients with severe hypercholesterolemia (>8.5 mmol/L) whereas our study included hypercholesterolemic patients with total cholesterol above 7.5 mmol/L.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations